Advanced Data Mining and Applications 19th International Conference, ADMA 2023, Shenyang, China, August 21-23, 2023, Proceedings, Part I - Yang, Xiaochun; Suhartanto, Heru.; Wang, Guoren; Wang, Bin.; Jiang, Jing.; Li, Bing.; Zhu, Huaijie; Cui, Ningning (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the refereed proceedings of the 19th International Conference on Advanced Data Mining and Applications, ADMA 2023, held in Shenyang, China, during August 21-23, 2023. The 216 full papers included in this book were carefully reviewed and selected from 503 submissions. They were organized in topical sections as follows: Data mining foundations, Grand challenges of data mining, Parallel and distributed data mining algorithms, Mining on data streams, Graph mining and Spatial data mining.
Time Series -- An Adaptive Data-Driven Imputation Model for Incomplete Event Series -- From Time Series to Multi-Modality: Classifying Multivariate Time Series via Both 1D and 2D Representations -- Exploring the Effectiveness of Positional Embedding on Transformer-based Architectures for Multivariate Time Series Classification -- Modeling of Repeated Measures for Time-to-Event Prediction -- A Method for Identifying the Timeliness of Manufacturing Data Based on Weighted Timeliness Graph -- STAD: Multivariate Time Series Anomaly Detection Based on Spatio-temporal Relationship -- Recommendation I -- Refined Node Type Graph Convolutional Network for Recommendation -- Multi-level Noise Filtering and Preference Propagation Enhanced Knowledge Graph Recommendation -- Enhancing Knowledge-aware Recommendation with Contrastive Learning -- Knowledge-Rich Influence Propagation Recommendation Algorithm Based on Graph Attention Networks -- A Novel Variational Autoencoder with Multi-Position Latent Self-Attention and Actor-Critic for Recommendation -- Fair Re-ranking Recommendation Based on Debiased Multi-Graph Representations -- Information Extraction -- FastNER: Speeding Up Inferences for Named Entity Recognition Tasks -- CPMFA: A Character Pair-Based Method for Chinese Nested Named Entity Recognition -- STMC-GCN: A Span Tagging Multi-Channel Graph Convolutional Network for Aspect Sentiment Triplet Extraction -- Exploring the Design Space of Unsupervised Blocking with Pre-trained Language Models in Entity Resolution -- Joint Modeling of Local and Global Semantics for Contrastive Entity Disambiguation -- Fine-grained Review Analysis using BERT with Attention: A Categorical and Rating-based Approach -- Emotional Analysis -- Discovery of Emotion Implicit Causes in Products based on Commonsense Reasoning -- Multi-modal Multi-emotion Emotional Support Conversation -- Exploiting Pseudo Future Contexts for Emotion Recognition in Conversations -- Generating Enlightened Suggestions based on Mental State Evolution for Emotional Support Conversation -- Deep One-Class Fine-Tuning for Imbalanced Short Text Classification in Transfer Learning -- EmoKnow: Emotion- and Knowledge-oriented Model for COVID-19 Fake News Detection -- Popular Songs: The Sentiment Surrounding the Conversation -- Market Sentiment Analysis based on Social Media and Trading Volume for Asset Price Movement Prediction -- Data Mining -- Efficient mining of high utility co-location patterns based on a query strategy -- Point-level Label-free Segmentation Framework for 3D Point Cloud Semantic Mining -- CD-BNN: Causal Discovery with Bayesian Neural Network -- A Preference-based Indicator Selection Hyper-heuristic for Optimization Problems -- An Elastic Scalable Grouping for Stateful Operators in Stream Computing Systems -- Incremental natural gradient boosting for probabilistic regression -- Discovering Skyline Periodic Itemset Patterns in Transaction Sequences -- Double-optimized CS-BP Anomaly Prediction for Control Operation Data -- Bridging the Interpretability Gap in Coupled Neural Dynamical Models -- Multidimensional Adaptative kNN Over Tracking Outliers (Makoto) -- Traffic -- MANet: An End-to-End Multiple Attention Network for Extracting Roads around EHV Transmission Lines from High-Resolution Remote Sensing Images -- Deep Reinforcement Learning for Solving the Trip Planning Query -- MDCN: Multi-Scale Dilated Convolutional Enhanced Residual Network for Traffic Sign Detection -- Identifying Critical Congested Roads based on Traffic Flow-Aware Road Network Embedding -- A Cross-Region-based Framework for Supporting Car-Sharing -- Attention-based Spatial-Temporal Graph Convolutional Recurrent Networks for Traffic Forecasting -- Transformer Based Driving Behavior Safety Prediction For New Energy Vehicles -- Graph Convolution Recurrent Denoising Diffusion Model for Multivariate Probabilistic Temporal Forecasting -- A Bottom-Up Sampling Strategy for Reconstructing Geospatial Data from Ultra Sparse Inputs -- Recommendation II -- Feature Representation Enhancing by Context Sensitive Information in CTR Prediction -- ProtoMix: Learnable Data Augmentation on Few-shot Features with Vector Quantization in CTR Prediction -- When Alignment Makes a Difference: A Content-Based Variational Model for Cold-Start CTR Prediction -- Dual-Ganularity Contrastive Learning for Session-based Recommendation -- Efficient Graph Collaborative Filtering with Multi-layer Output-enhanced Contrastive Learning -- Influence Maximization with Tag Revisited: Exploiting the Bi-Submodularity of the Tag-Based Influence Function -- Multi-Interest Aware Graph Convolution Network for Social Recommendation -- Enhancing MultimediaRecommendation through Item-Item Semantic Denoising and Global Preference Awareness -- Resident-based Store Recommendation Model for Community Commercial Planning.c.
Keywords: Data mining; Computer vision; Computer systems; Education -- Data processing; Application software; Artificial intelligence; Data Mining and Knowledge Discovery; Computer Vision; Computer System Implementation; Computers and Education; Computer and Information Systems Applications; Artificial Intelligence